A taxonomic review of genus Scipinia Stål (Hemiptera: Reduviidae: Harpactorinae) from China - Huang, Xia; Zhao, Ping; Zhou, Shanyi; Cai, Wanzhi (Zootaxa, 2007)
The Chinese species of the reduviid genus Scipinia (subfamily Harpactorinae) are reviewed, keyed, and illustrated. Three species of this genus are recognized from China. Scipinia rotunda is described as new to science. Diagnostic redescriptions of the two known species, S. horrida Stål and S. subula Hsiao & Ren, are provided. The diagnostic characters of the genus are slightly modified.